Feasibility Test of Refill Drinking Water in Batam - Hazimah, Hazimah; Triwuri, Nurlinda Ayu (-)
According to the Regulation of the Minister of Health No.492 Year 2010, drinking water quality is assessed from the chemistry parameters, one of them is aluminium (Al), iron (Fe), kloride (Cl) and copper (Cu), it should meet the standards that have been defined. The aim of this research is to find out the quality of refill drinking water in Batam with indicator aluminium (Al), iron (Fe), kloride (Cl) and copper (Cu). The research was conducted in the laboratory of PT. Sucofindo Batam, Riau Islands-Indonesia. The type of this research is laboratory descriptive. Data was obtained by using simple randomized sampling technique. Aluminium (Al), iron (Fe), cloride (Cl) and copper (Cu) research of drinking water used Standart Methods for Water and Waste Water American Public Health Assosiation, 22nd eddition 201. The result of this research showed that all six samples meet the qualification of the Regulation of the Minister of Health No.492 Year 2010 by chemistry parameters of Aluminium (Al), iron (Fe), cloride (Cl) and copper (Cu).